Consumer Behavior as a Potential Acceptance of Renewable Energy Source in Indonesia - Fitria Avicenna; Nufian S Febriani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
The trend of using renewable energy (RE) as a substitute for fossil energy is increasing as the issue of global warming continues to be echoed. Previous studies about RE focusing much on the availability and infrastructure of RE, yet no study about potential acceptance of RE in Indonesia has been conducted. Therefore, this study will fill the gap in the topic of RE consumer behavior. Qualitative approach was used in this study, by conducting literature reviews to relevant studies about consumer behavior towards RE in various countries. The results show that income, education level, infrastructure, and government policies will have a major influence in the transition process. The government occupies a strategic position with the authority in terms of supportive policies, fulfillment of infrastructure, and education of the public as potential consumers. Two scenarios are proposed for starting a shifting energy campaign in Indonesia. Finally, this study aims to enrich the contribution of communication science in the field of energy security. It can also be a reference for comparison for similar studies that focus on communication issues related to RE.